2004
DOI: 10.1038/nature02293
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic dynein functions as a gear in response to load

Abstract: Cytoskeletal molecular motors belonging to the kinesin and dynein families transport cargos (for example, messenger RNA, endosomes, virus) on polymerized linear structures called microtubules in the cell. These 'nanomachines' use energy obtained from ATP hydrolysis to generate force, and move in a step-like manner on microtubules. Dynein has a complex and fundamentally different structure from other motor families. Thus, understanding dynein's force generation can yield new insight into the architecture and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
509
12
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(590 citation statements)
references
References 29 publications
62
509
12
7
Order By: Relevance
“…In [242], it was reported that under no load, dyneins were taking predominantly 24-and 32-nm long steps, and that the step length was decreasing under load. Later, more direct measurements of dynein displacement were performed through high temporal resolution fluorescence.…”
Section: Dyneinmentioning
confidence: 99%
“…In [242], it was reported that under no load, dyneins were taking predominantly 24-and 32-nm long steps, and that the step length was decreasing under load. Later, more direct measurements of dynein displacement were performed through high temporal resolution fluorescence.…”
Section: Dyneinmentioning
confidence: 99%
“…The centre of the head would appear to move an even shorter distance; 3.7nm has been measured for axonemal dynein [48]. However, if the dynein stalk were to flex towards the minus end while first making an attachment (conformation shown dotted in step 6) instead of pointing at 90° to the MT, the cargo could subsequently be moved by 16nm; 24nm shifts also reported during movement under low loads [59] could possibly be produced by simultaneously flexing the bound stalk in the other direction (conformation shown by dotted line in step 3).…”
Section: Discussionmentioning
confidence: 87%
“…Since the stepping motion of kinesin was first observed by a single-molecule experiment [1], similar discrete motions of various molecular motors have been reported [2][3][4][5]. Singlemolecule techniques [6,7] have shed light on the mechanisms of these tiny biological motors.…”
Section: Introductionmentioning
confidence: 98%